Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain Et Causa Ischialgia Di RSUD Kab. Sukoharjo - Putri, Mahardika Indeswari, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2016)
Background: Low Back Pain is an unpleasant condition with has functional limit and pain if someone do movement or mobility. Use of modality like Infrared, Transcutaneus Electrical Nerve Stimulation, William flexion can cope the case related with reducing pain, increase Range of Motion of trunk and hip, increasing muscle strength. Aim: to understand management physiotherapy to reducing pain, increasing range of motion, increasing muscle strength, increasing functional abilities in the case LBP et causa Ischialgia with modality Infrared, TENS, William Flexion. Results: a woman 19 years old with diagnose LBP et cause Ischialgia after having management physiotherapy (Infrared, TENS, William Flexion) more or less 1 month every other day, 15 minutes eachother, having reduce painful silence wiyh VAS T1=2,3 cm, a T6=0 cm, tenderness painful T1=4,7 cm,aT6=2,5 cm, movement painful T1=5,3 cm, a T6=3 cm. Having increase MMT Abdominal T1=3 , a T6=4.Having increase MMT Hip with muscle groups flexor, extensor, abductor, adductor T1= 3, a T6= 4. Having increase S:T1= 50-00-400, a T6= 250-00-1100, F: T1=200-00-100, a T6=250-00-150, R=350-00-350. Conclusion: Infrared, Transcutaneus Electrical Nerve Stimulation, William flexion can cope the case related with reducing pain, increase Range of Motion of trunk and hip, increasing muscle strength. Key Word: Low Back Pain, Ischialgia, Infrared, TENS, William Flexion.